2007
DOI: 10.22488/okstate.18.100356
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellianism and Personality Typing as Determinants for Screening Commercial Pilot Candidates

Abstract: The association between personality and effective team leadership in the cockpit environment has been a major focus of research in aviation management. The major air carriers incorporate in their assessment process personality style and decision-making skills by placing pilot candidates through a two or three stage interview process. In an ongoing effort to develop a comprehensive pilot candidate selection model, university researchers have studied the relationship between personality type and skill in small g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Through the use of the MBTI, three strong categories were confirmed twenty-one percent of the sample showed the profile of extraversion, sensing, thinking and judging (ESTJ) type. This conforms to Hamilton's (2007) study of civil commercial pilots which also displayed the same dominance in the ESTJ category type. The second highest at 10.3% was categorised as introverted, sensing, thinking and judging (ISTJ), while the third largest group also at 10.3% held extroversion, sensing, thinking and perceiving (ESTP).…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Through the use of the MBTI, three strong categories were confirmed twenty-one percent of the sample showed the profile of extraversion, sensing, thinking and judging (ESTJ) type. This conforms to Hamilton's (2007) study of civil commercial pilots which also displayed the same dominance in the ESTJ category type. The second highest at 10.3% was categorised as introverted, sensing, thinking and judging (ISTJ), while the third largest group also at 10.3% held extroversion, sensing, thinking and perceiving (ESTP).…”
supporting
confidence: 86%
“…The pilot profile also describes the individual as active with high levels of assertiveness. Through the use of the Myers-Briggs Type Indicator (MBTI), Hamilton (2007) provided dimensional profiles of 52 commercial flight officers. It was concluded that there was a significant personality type with successful informal group leaders holding dimensions of either extroversion, intuition, thinking and judging (ENTJ) or extroversion, sensing, thinking and judging (ESTJ) within the MBTI category.…”
mentioning
confidence: 99%
See 2 more Smart Citations